Axle Box Resonance Excitation Model Based on Wheelset Polygon and Its Resonance Characteristic Analysis in High‐Speed Train. Issue 12 (15th November 2022) - Yi, Cai; Huo, Haoxiang; Liao, Xiaokang; Wang, Hao; Lin, Jianhui
Abstract: By grasping the vibration characteristics of the wheelset, the service state of the wheel can be reversely deduced. In this paper, the dynamic model of a rigid–flexible coupling vehicle system, considering wheelset flexibility and axle box flexibility, is established, and a novel resonance excitation loading method for axle box is proposed. Through this method, the vertical force of the wheel‐rail and the resonance response of the axle box vibration under different rigid–flexible combinations of wheelset axle box are obtained. The resonance response characteristics of the axle box of the wheelset and the main factors affecting the resonance characteristics are analyzed. Results show that the bending mode of the wheelset considerably affects the vibration characteristics of the axle box. The mass, the moment of inertia around the x ‐axis, and the position of the center of gravity of the axle box also greatly affect the resonance characteristics of the wheel‐to‐axle box. Abstract : By grasping the vibration characteristics of the wheelset, the service state of the wheel can be reversely deduced. In this paper, the dynamic model of a rigid–flexible coupling vehicle system, considering wheelset flexibility and axle box flexibility, is established, and a novel resonance excitation loading method for axle box is proposed.